Tests of the Chronic Shortage Hypothesis: The Case of Poland - Portes, Richard (The Review of Economics and Statistics, 1988)
In the analysis of econometric disequilibrium models, it is common to test the n ull hypothesis of "equilibrium" against the "disequilibrium" alternat ive. This paper tests the null hypothesis of "all-excess-demand"-tha all observations correspond to (positive) excess demand-against the alternative that permits excess demand of either sign. The auth ors use a test due to Rogers (1984), which their Monte Carlo experime nts suggest performs well in small samples, as well as a "quasi-like lihood ratio test, " which is a suggestive heuristic procedure. The da ta are from the aggregate consumption goods market in Poland 1955-80, and the paper is, thus, a test of J. Kornai's assertion that "chroni c shortage" characterizes such CPEs. The results conclusively reject the "all-excess-demand" hypothesis for the Polish case, and the Rogers test promises to be of considerable practical use. Copyright 1988 by MIT Press.